Aspectos epidemiológicos clássicos e moleculares de infecções por Staphylococcus aureus suscetível a meticilina (MSSA) em uma Unidade de Terapia Intensiva Neonatal de um Hospital Universitário brasileiro - Silva, Helisângela de Almeida (2007)
Neonatal Intensive Care Unit is the unit in which hospital infectious problems (HI) are the most significant ones, due to high frequency of intrinsic e extrinsic risk factors. Two investigations were performed. The first of them was a retrospective study from January, 2001 to December, 2003, whose aim was to compare hospital infection rates before, during and after a unit reform; the second one was a prospective search that analyzed infection incidence and colonization respective prevalence for Staphylococcus aureus. The first study showed a significant 12.8 to 18.6 increase on hospital infection rate, after the removal to a temporary location as well a more expressive decline (p<0,001) in catheter-related bacteremia after the removal to new unit, in spite of an increased central vascular catheter utilization density (CVC) from 0.18 to 0.55 in both periods. This difference has simultaneously occurred with the substitution of vein dissection CVC insertion technique (phlebotomy) by the employment of a peripheral insertion catheter (PICC). In the second phase of the investigation, staphylococcus infections were detected by laboratorial and NNISS vigilance techniques. The detected incidence rates for hospital infection was 23/1000 patient/day. From 32 evaluated newborn, 17 were infected and 15 colonized. Sepsis was the most frequent infectious syndrome (61%) and the nose was the most colonized site (66%). Antibiotic use showed to be the only significant variable for S. aureus infection. Risk factors by univariate analysis were the following ones: antibiotics use, central vascular catheter (CVC) utilization, CVC use for more than seven days and phlebotomy insertion. This was the only significant variable by multivariate analysis. Molecular analysis of 37 samples showed a policlonality (12 genotypes), and B clone prevailed (34%) over the other ones. Clone identity was observed in all cases in which it was possible to determinate the relationship between colonizing and infecting samples. The pvl gene was detected in four colonizing samples. MSSA infection was associated to previous colonizing by pathogen, with evidence of horizontal transmission among newborn, in function of B clone prevailing as well micro-clusters occurrence in the unit.